2010
DOI: 10.1161/atvbaha.109.199448
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hemostasis and Decline in Cognitive Function in Older People

Abstract: Objective-To determine whether activation of hemostatic function (thrombosis and fibrinolysis) is associated with cognitive decline in older people. Methods and Results-We studied 5804 people (age, 70 -82 years) Key Words: aging Ⅲ cognition Ⅲ fibrinolysis Ⅲ stroke Ⅲ thrombosis V ascular disease is an important and potentially preventable contributor to cognitive decline and dementia in older people. 1 Postmortem studies have shown that Alzheimer pathology is important; however, on its own it is often not suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
2
33
1
1
Order By: Relevance
“…17,18 CRP was measured at baseline with an automated particle-enhanced immunoturbidimetric assay (Roche UK). 17 Heart failure hospitalization and cardiovascular mortality…”
Section: Inflammation and Endothelial Dysfunction Markersmentioning
confidence: 99%
“…17,18 CRP was measured at baseline with an automated particle-enhanced immunoturbidimetric assay (Roche UK). 17 Heart failure hospitalization and cardiovascular mortality…”
Section: Inflammation and Endothelial Dysfunction Markersmentioning
confidence: 99%
“…The central finding was that increased levels of D-dimer and prothrombin fragment 1ϩ2 (ie, markers of thrombin generation) were associated independently with increased rates of cognitive decline and deterioration in activities of daily living (Table). 12 Interestingly, markers of endothelial dysfunction (eg, tissue plasminogen activator and von Willebrand factor) were not associated with cognitive decline.…”
Section: See Accompanying Articles On Pages 599 and 605mentioning
confidence: 98%
“…Oral anticoagulation with warfarin might be attractive because it reduces prothrombin fragment 1ϩ2, thrombin-antithrombin complexes, and D-dimer 12 ; safety concerns exist about its use in patients with leukoaraiosis 16 (ie, the group in whom it might be useful). Information from completed and ongoing trials of oral direct thrombin inhibitors, in which data on cognition were collected, will further illuminate this issue.…”
Section: See Accompanying Articles On Pages 599 and 605mentioning
confidence: 99%
“…Various cohort and case-control-based studies have described an apparent association between higher levels of blood markers of thrombosis and haemostasis and incident dementia or cognitive decline (Bots et al 1998;Gallacher et al 2010;Stott et al 2010). Recent systematic review and meta-analysis have confirmed this link with blood markers; observed associations were strongest for Bvascular^dementia but also apparent for Ballcause^(undifferentiated) dementias (Quinn et al 2011).…”
Section: Introductionmentioning
confidence: 97%